Analisis Didaktis untuk Meningkatkan Hasil Belajar Calon Guru Fisika Ditinjau dari Gaya Kognitif dan Gaya Belajar - Ahmad Busyairi; Ahmad Harjono; Muhammad Zuhdi (Kappa Journal, 2021)
This study aims to analyze the learning outcomes of prospective physics teachers in terms of cognitive and learning styles. The sample consisted of 47 prospective physics teachers at the University of Mataram. The instruments used consisted of the Group Embedded Figures Test (GEFT), the VAK learning style questionnaire, and the learning outcomes test instrument. The research data were then categorized and analyzed using descriptive statistics to see a picture of student learning outcomes in terms of their learning styles and cognitive styles. Based on the results of data analysis, it can be seen that there are differences in learning outcomes between students who have a field independence (FI) cognitive style and students who have a field dependence (FD) cognitive style. Students who have FI cognitive style tend to get better scores when compared to FD. When viewed from the learning style, it can be seen that the number of students who have visual learning styles is 46.80%, audio is 8.51%, and kinesthetic is 44.68%. Students who have a kinesthetic learning style tend to get better scores when compared to students who have a visual and audio learning style. By paying attention to the characteristics and percentage of students who have FI and FD cognitive styles and students who have visual, audio, and kinesthetic learning styles, one alternative learning that can be used to improve student learning outcomes is cooperative or experimental-based collaborative learning model.